Rancang Bangun Film Animasi 3D Sejarah Terbentuknya Kerajaan Samudra Pasai Menggunakan Software Blender - Kurniyatul Ainiyah; Nurul Hidayah; Faradilah Putri Damayanti; Indana Nuril Hidayah; Juniardi Nur Fadila; Fresy Nugroho (JISKA (Jurnal Informatika Sunan Kalijaga), 2020)
Indonesian people's knowledge about the history of kingdoms in Indonesia was decreased. Now the existence of history books was shifted by the rapid development of technology. Realized this, many educational institutions were involved in technology to their learning media. To support that, the writer will use technology to create a learning media, named 3D short animated films. This kind of film turned out to attract the publics' attention, ranging from children to adolescents. The animated film will be designed with the theme of the first Islamic kingdom in Indonesia, named the Samudra Pasai kingdom with a duration of approximately 3 minutes. this animated film was made by Blender software version 2.79. The design of this animation aims to increase knowledge as well as learning media for students about the history of the Indonesian people, especially the history of Samudra Pasai kingdom.